Hubungan Aktivitas Fisik terhadap Tingkat Kecemasan Selama Masa Pandemi COVID-19: Scoping Review - Sayida Nafisa; Mia Kusmiati; Panca Bagja Mohamad (Bandung Conference Series: Medical Science, 2022)
Abstract. During the COVID-19 pandemic, social restrictions and self-isolation policies were carried out to prevent and reduce the number of COVID-19 diseases. These policies led to the closure of various public facilities such as schools, offices, fitness centers, places of worship, etc. So that it has an impact on the level of physical and psychological activity. The purpose of this study was to assess how physical activity affects anxiety levels and what types of physical activity can be done during the quarantine period of the COVID-19 pandemic. This study was conducted with a scoping review approach. The databases used are PubMed, ProQuest, ScienceDirect, and SpringerLink with several keywords including Exercise (OR “Physical Activity”) AND Anxiety Disorder AND Self Isolation, and Physical Activity AND Anxiety AND Pandemic Covid 19 AND Self Isolation, as well as Physical Activity AND Anxiety Disorder AND Pandemic Covid 19 Self Isolation. The search for selected articles starts from 2019 – 2021 with a research design that is a cross-sectional study. The total journals obtained were 30495 articles which were then screened using PICOS, and 10 articles were obtained. There are 10 articles that meet the eligible criteria based on critical appraisal using JBI's critical appraisal tools. The results found in 4 selected articles showed that physical activity had a positive effect on reducing anxiety symptoms. Hypothalamic Pituitary-Adrenal (HPA) and brain-derived neurotrophic factor (BDNF) are said to play a role in this. Moderate to vigorous physical activity is said to reduce symptoms of anxiety. Abstrak. Selama masa pandemi COVID – 19, kebijakan pembatasan sosial dan isolasi mandiri dilakukan untuk mencegah dan mengurangi jumlah penyakit COVID – 19. Kebijakan tersebut menyebabkan penutupan berbagai sarana fasilitas publik seperti sekolah, kantor, pusat kebugaran, tempat ibadah, dll. Sehingga hal tersebut berdampak terhadap tingkat aktivitas fisik dan psikologis. Tujuan dari penelitian ini adalah untuk menilai bagaimana pengaruh aktivitas fisik terhadap tingkat kecemasan dan apa jenis aktivitas fisik yang dapat dilakukan selama masa karantina pandemi COVID – 19. Penelitian ini dilakukan dengan pendekatan scoping review. Database yang digunakan yaitu PubMed, ProQuest, ScienceDirect, dan SpringerLink dengan beberapa kata kunci diantaranya Exercise (OR “Physical Activity”) AND Anxiety Disorder AND Self Isolation, dan Physical Activity AND Anxiety AND Pandemic Covid 19 AND Self Isolation, serta Physical Activity AND Anxiety Disorder AND Pandemic Covid 19 Self Isolation. Pencarian artikel yang dipilih yaitu dimulai dari tahun 2019 – 2021 dengan desain penelitian yaitu cross-sectional study. Total jurnal yang didapatkan yaitu 30495 artikel yang kemudian dilakukan screening dengan menggunakan PICOS, dan didapatkan 10 artikel. Terdapat 10 artikel yang memenuhi kriteria eligible berdasarkan critical appraisal dengan menggunakan JBI’s critical appraisal tools. Hasil yang ditemukan pada 4 artikel yang terpilih menunjukan bahwa aktivitas fisik memiliki pengaruh positif dalam menurunkan gejala kecemasan. Hypothalamic Pituitary-Adrenal (HPA) dan brain-derived neurotrophic factor (BDNF) disebut berperan dalam hal ini. Aktivitas fisik sedang hingga berat dikatakan mampu menurunkan gejala kecemasan.